The developmental transcription factor IRF6 attenuates ABCG2 gene expression and distinctively reverses stemness phenotype in nasopharyngeal carcinoma. (1st September 2018) - Xu, Liang; Huang, Tie-Jun; Hu, Hao; Wang, Meng-Yao; Shi, Si-Mei; Yang, Qin; Lin, Fen; Qiang, Yuan-Yuan; Mei, Yan; Lang, Yan-Hong; Li, Chang-Zhi; Peng, Li-Xia; et al.
Abstract: Nasopharyngeal carcinoma (NPC), which originates from the nasopharynx, is highly prevalent in Southern China and Southeast Asia, and more than 90% of all NPCs are non-keratinizing undifferentiated cells or poorly differentiated squamous cells. Cancer stem cells (CSCs) are capable of self-renewal and have differentiation potential. These properties form the basis of cancer initiation, development, and radiochemoresistance. However, the molecular mechanisms underlying NPC CSC maintenance remain poorly understood. Here, genomic expression profiling using our previously established monoclonal cellular and animal models revealed that interferon regulatory factor 6 ( IRF6 ) was downregulated in highly metastatic NPC cells, cancer stem-like NPC cells and animal models. Functional assays revealed that elevated IRF6 expression suppressed cell proliferation, growth, CSCs properties and enhanced cell chemotherapeutic sensitivity. However, silencing IRF6 resulted in opposing effects. Moreover, we determined that as a tumor suppressor gene and transcription factor, IRF6 directly bound the upstream region o f the ATP-binding cassette sub-family G member 2 ( ABCG2 ) DNA element and suppressed target ABCG2 expression in NPC cells. Consistently, an inverse correlation was observed between the mRNA levels of IRF6 and ABCG2 in clinical NPC samples. With these results, we provide the first evidence that IRF6 directly targets the ABCG2 gene and selectively kills CSCs in NPC and that IRF6 may be a valuable tool for developing new CSC-targeted treatment strategies for undifferentiated NPC patients. Highlights: IRF6 is initially found to be down regulated in our well established high-metastasis NPC cellular clone, and further series functional studies confirmed that IRF6 can inhibit the growth, migration, invasion, and metastasis of NPC cells. Elevated IRF6 expression can enhance NPC chemotherapeutic sensitivity. IRF6 down-regulates the expression of ABCG2 in NPC. IRF6 can selectively kill nasopharyngeal carcinoma stem cells and overexpression of IRF6 is a promising approach for anti-stem cell targeted therapy.